Konsep Estetika Jepang: Corak Naturalis yang Dijiwai oleh Tradisi, Kepercayaan, dan Alam - Parmono, Kartini (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 1999)
The Japanese Aesthetics concept is a blend of traditions, beliefs, and nature. This research was conducting by studying literature and the collected was analyzed by using interpretation method.The result of the study that the starting point of the Japanese Aesthetics is nature. Japanese believe that daily natural phenomenon such as sun, moon, mountain, water fail, and trees is believed to have or souls